A new semi-solid casting technique for fabricating SiC-reinforced Mg alloys matrix composites. (1st June 2016) - Esmaily, M.; Mortazavi, N.; Svensson, J.E.; Halvarsson, M.; Wessén, M.; Johansson, L.G.; Jarfors, A.E.W.
Abstract: The capability of the newly developed rheocasting (RC) technique in combination with the RheoMetal process for producing SiC particulate-reinforced AM50 and AZ91D matrix composites (Mg-based MMCs) was investigated. The quality of the MMCs was studied by analyzing the fraction of casting pores, number density of SiC clusters and the uniformity of SiC particles. Solid fraction, particle size and oxidation of SiC particles had strong impacts on the overall quality of the MMCs. The MMCs produced by 40% solid fraction and oxidized micron-sized SiC particles exhibited an excellent casting quality. A low-quality MMC was obtained when non-oxidized sub-micron sized SiC particles were employed. The results showed the formation of various types intermetallic particles and carbides such as MgO, Mg2 Si, Al2 MgC2, Mg2 C3, Al4 C3 as the interfacial reaction products of SiC/Mg alloy's melts. Mg hydride (α-MgH2 ) was also identified in inter-dendritic regions of the MMCs for the first time.